2008
DOI: 10.1016/j.febslet.2008.06.036
|View full text |Cite
|
Sign up to set email alerts
|

P‐glycoprotein down‐regulates expression of breast cancer resistance protein in a drug‐free state

Abstract: This study investigated whether P-glycoprotein (Pgp) and breast cancer resistance protein (BCRP) are linked in terms of expression. RT-PCR and Western blot analyses showed that the lung cancer cell line SK-MES-1/WT expressed BCRP. In a drug-free state, BCRP expression was significantly down-regulated in doxorubicin-resistant SK-MES-1/DX1000 cells overexpressing Pgp. Pharmacological inhibitors (PSC833 or verapamil) or siRNA for Pgp inhibited the down-regulation of BCRP, which was confirmed by confocal microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…In our current study, for the first time, we have confirmed that overexpression of miR200c decreased the levels of JNK2, p-JNK, p-c-Jun, ABCB1/P-gp, and MMP-2/-9 in MDR colorectal cancer cells. In addition, our analyses showed that miR200c did not affect other critical transporters in MDR such as MRP-1, MRP-2, and BCRP, consistent with the reported function of JNK (39)(40)(41). We also found that ATF-2 and Elk-1, the other two major players downstream of activated JNK in MDR colorectal cancer cells, were not affected by miR200c on the expression levels, suggesting that miR200c might selectively target the JNK2/p-JNK/p-c-Jun signaling pathway.…”
Section: Discussionsupporting
confidence: 73%
“…In our current study, for the first time, we have confirmed that overexpression of miR200c decreased the levels of JNK2, p-JNK, p-c-Jun, ABCB1/P-gp, and MMP-2/-9 in MDR colorectal cancer cells. In addition, our analyses showed that miR200c did not affect other critical transporters in MDR such as MRP-1, MRP-2, and BCRP, consistent with the reported function of JNK (39)(40)(41). We also found that ATF-2 and Elk-1, the other two major players downstream of activated JNK in MDR colorectal cancer cells, were not affected by miR200c on the expression levels, suggesting that miR200c might selectively target the JNK2/p-JNK/p-c-Jun signaling pathway.…”
Section: Discussionsupporting
confidence: 73%
“…We discovered that certain ER stress inducers (tunicamycin and THAPS) could increase recombinant ABC transporter expression. It has been shown that these agents can induce P-gp mRNA and protein expression (Bark et al, 2008). The concentration of the compounds we used did not compromise the TEER resistance of the cell monolayer.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study showed that ABCG2 expression was suppressed in the presence of P-gp in HeLa cells (Shukla et al, 2012), and it was suggested that expression of Pgp and ABCG2 is somewhat linked (Bark et al, 2008). Therefore, we investigated whether P-gp and breast cancer resistance protein expression is affected in the polarized cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found an inverse relation between ABCB1 and ABCG2 expression in the absence of doxorubicin [43]. Similarly, Cisternino et al [44] found that defective ABCB1 was associated with increased ABCG2 mRNA at the mouse blood-brain barrier.…”
Section: Discussionmentioning
confidence: 96%